Repeated versus single measurement of plasma omega-3 fatty acids and risk of heart failure - Djoussé, Luc (2014)
PURPOSE: Studies have previously examined the relation between a single measure of plasma fatty acids and risk of heart failure. However, it is unclear whether the use of repeated measures of fatty acids over time is required for the assessment of omega-3 fatty acids-heart failure relation. METHODS: Using a nested case-control design, this ancillary study used 421 cases and 421 matched controls from the Physicians’ Health Study to assess the variability of plasma phospholipid fatty acids over time and compare the results of omega-3 fatty acids-heart failure associations using a single versus repeated measurements of plasma phospholipid fatty acids. Plasma omega-3 fatty acids were measured at baseline (1982) and approximately 15 years later using gas chromatography. RESULTS: Spearman correlation coefficients between baseline and follow-up measures of α-linolenic acid (ALA), EPA, DPA, and DHA were 0.20, 0.45, 0.28, and 0.50, respectively, in the control series. Multivariable adjusted odds ratios for heart failure per standard deviation higher plasma ALA were 0.98 (95% CI: 0.85-1.13) when using baseline ALA and 0.86 (95% CI: 0.74-1.01) when using the average of baseline and follow-up ALA measurements. Corresponding odds ratios for total long chain omega-3 FAs (EPA + DHA + DPA) were 0.87 (0.73-1.03) and 0.88 (0.75-1.04). CONCLUSIONS: Our data demonstrate modest correlation between measurements of plasma phospholipid fatty acids spaced by 15 years. A single measurement of plasma phospholipid fatty acids appears reasonable to estimate the risk of heart failure over long-term follow up.